The Effects of Production-Oriented Approach on Chinese Vocational College Students’ English Speaking Ability - Yang, Jue; Chayanuvat, Anchalee (International Journal of Multidisciplinary in Management and Tourism, 2024)
This study aimed to 1) explore whether Production-Oriented Approach in teaching speaking English in higher education could improve the Chinese vocational college students’ speaking ability; and 2) investigate whether Chinese college students were satisfied with Production-Oriented Approach for oral English lessons. The study was conducted at a Chinese vocational college in Yunnan province, China. The quasi-experimental group of 48 students was selected by convenience sampling method. The instruments adopted in the study consisted of the Pre/Post-Test and a satisfaction questionnaire. The Pre/Post Test result revealed a significant improvement of the Chinese vocational college students’ speaking ability scores in the five parts of fluency, pronunciation, grammar, vocabulary and content (P< 0.05). The questionnaire data analysis indicated that the students were satisfied with the Production-Oriented Approach in teaching and learning English speaking at the level of ’Agree’ (X=3.880/SD-1.188). Thus, it is recommended the teacher should focus on developing students’ speaking ability and help them improve their speaking skills and students learning strategies under the guidance of the production-oriented approach as well as the exploration of teacher-student interaction. This study provides valuable information about the impact of teaching English in higher education on improving the speaking ability of higher vocational college students as well as students’ satisfaction with teaching English as a foreign language. These findings have important implications for future teaching research and practice, which will help promote the development of English teaching and improve the speaking ability of higher education college students.